2002
DOI: 10.1086/339933
|View full text |Cite|
|
Sign up to set email alerts
|

Reduced-Median-Network Analysis of Complete Mitochondrial DNA Coding-Region Sequences for the Major African, Asian, and European Haplogroups

Abstract: The evolution of the human mitochondrial genome is characterized by the emergence of ethnically distinct lineages or haplogroups. Nine European, seven Asian (including Native American), and three African mitochondrial DNA (mtDNA) haplogroups have been identified previously on the basis of the presence or absence of a relatively small number of restriction-enzyme recognition sites or on the basis of nucleotide sequences of the D-loop region. We have used reduced-median-network approaches to analyze 560 complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
507
1
7

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 467 publications
(540 citation statements)
references
References 47 publications
25
507
1
7
Order By: Relevance
“…(2009)641641 IndianHerrnstadt et al. (2002)560435 European, 56 African, 52 Native American, 17 AsianIngman et al. (2000)53African, European, Asian, New WorldTotal9413

Permissions:

John Wiley & Sons, Ltd

…”
Section: Abstract Of Appendixmentioning
confidence: 99%
“…(2009)641641 IndianHerrnstadt et al. (2002)560435 European, 56 African, 52 Native American, 17 AsianIngman et al. (2000)53African, European, Asian, New WorldTotal9413

Permissions:

John Wiley & Sons, Ltd

…”
Section: Abstract Of Appendixmentioning
confidence: 99%
“…They reported a frequent occurrence (81/181) of heteroplasmy at this position in different patients but also documented a considerable frequency of the bvariant-rich fractionQ in the control group (43/184). The latter finding, however, is significantly at variance with a large database of mtND4 sequences (Finnilä et al, 2001;Herrnstadt et al, 2002;Kong et al, 2003), where position 12027 is completely invariable and unambiguous (0/800; pb0.001). In their claim that T12027C played a significant role in schizophrenia, Marchbanks et al (2003) evidently overlooked that there is a high risk of incomplete digestion by the restriction enzyme even with a 100% homoplasmic sample.…”
mentioning
confidence: 72%
“…This mutation, previously observed by Thomas et al (1996) was found to be in connection with A12308G (a marker for mtDNA haplogroup U), T3197C (a marker for haplogroup U5), and T5814C (which was associated with mitochondrial encephalopathy; Manfredi et al, 1996) in a patient with limb myopathy (Sternberg et al, 1998). Indeed, it is now well known that a transition at position 5656 (which is located as a non-coding spacer between the tRNA Ala and tRNA Asn genes) is characteristic of a sub-haplogroup (now referred to as U5b1; Tambets et al, 2004) of the European haplogroup U5b (Finnilä et al, 1999(Finnilä et al, , 2001Herrnstadt et al, 2002). Phylogenetic information is thus a useful guide to the evaluation of pathogeneity of a particular mutation, especially since the database of complete mtDNA sequences is rapidly growing; e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This pathogenic variation substitutes a highly conserved neutral polar amino-acid residue to a basic polar residue (p.Tyr19His) and has been reported to cause a major defect in COX assembly. 26 Secondly, the m.7080T4C missense variation, which changes a neutral apolar residue to one with similar polarity (p.Phe393Leu), has previously been reported as both a polymorphism in haplogroups U 27 and M12b, 28 as well as a prostate cancer-associated point mutation. 29 This substitution was identified at a homoplasmic frequency in a female patient who did not have a clear complex IV deficiency, but a combined deficiency of complexes I and III.…”
Section: Non-haplogroup-associated Mtdna Variantsmentioning
confidence: 98%